The producer's playbook : real people on camera - DeLouise, Amy (Routledge, 2016)
Producer's Playbook: Real People on Camera is a no-nonsense guide for producers looking to get the best performances from "real people" to tell powerful stories on video. Director/producer Amy DeLouise brings years of experience to this resource for creating the best on-screen impact with non-actors for interviews, re-enactments, documentary and direct-to-camera messages. With useful case studies and tips on everything from managing locations and budgeting to strategies for managing crews and the expectations of executive producers and clients, this is an invaluable resource for professionals working in reality TV, documentary, corporate video, and more. Ample case studies with perspectives from industry professionals interviewed by the author, as well as her own plentiful stories from the field Tips are featured in sidebars throughout the text, so that readers can see how the information applies to real situations Full-color photographs allow readers to visualize real world production situations The appendix includes useful templates and checklists for working producers.